An Introduction to Parthian Silver Fractions, the Little Anomalies of Arsacid Coinage - Robert Langnas, Bob (KOINON: The International Journal of Classical Numismatic Studies, 2018)
Although Parthian coins have appealed to a cross-section of ancient coin collectors for centuries, interest seems to have been particularly piqued by the 1993 publication of Fred B. Shore’s Parthian Coins & History: Ten Dragons Against Rome and by the subsequent sale of his collection in December 1995. Coins from the Parthian series present collectors with a number of different areas of potential focus, among them the different mint monograms, the varied representations of the distinctive Parthian tiara, portraits sporting the “royal wart” of the Arsacids, “off” style examples from Parthia’s eastern mints, etc.